2016
DOI: 10.1038/srep32786
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic commitment of human umbilical cord blood-derived mesenchymal stem cells in collagen matrices for cartilage engineering

Abstract: Umbilical cord blood (UCB) is a promising alternative source of mesenchymal stem cells (MSCs), because UCB-MSCs are abundant and harvesting them is a painless non-invasive procedure. Potential clinical applications of UCB-MSCs have been identified, but their ability for chondrogenic differentiation has not yet been fully evaluated. The aim of our work was to characterize and determine the chondrogenic differentiation potential of human UCB-MSCs (hUCB-MSCs) for cartilage tissue engineering using an approach com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…The ease of procurement, collection of large numbers, and favorable costs favor PB, BM, and AT in that order. The ultimate autologous stem cell option is of course UC blood and tissues, due to ease of collection, storage, costs, safety, and availability, but there have as yet not been any autologous uses in OA employing that source [35]. The only clinical comparative study between stem cell types in cartilage regeneration is the study of Skowroński and Rutka [36] showing superior results for PBSC versus BM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ease of procurement, collection of large numbers, and favorable costs favor PB, BM, and AT in that order. The ultimate autologous stem cell option is of course UC blood and tissues, due to ease of collection, storage, costs, safety, and availability, but there have as yet not been any autologous uses in OA employing that source [35]. The only clinical comparative study between stem cell types in cartilage regeneration is the study of Skowroński and Rutka [36] showing superior results for PBSC versus BM.…”
Section: Discussionmentioning
confidence: 99%
“…Potential feasible autologous stem cell sources for cartilage regeneration treatments include hematopoietic stem cells (HSCs) in bone marrow (BM), hG-CSF-activated/stimulated peripheral blood (PB) (the mainstay choice in stem cell collection and transplantation since many decades further ensuring patient safety [23]), and theoretically umbilical cord blood (UCB). Trabecular bone, cartilage, adipose tissue (AT), and, theoretically, umbilical cord (UC) tissues [35] also contain autologous stem cells with chondrogenic potential. The ease of procurement, collection of large numbers, and favorable costs favor PB, BM, and AT in that order.…”
Section: Discussionmentioning
confidence: 99%
“…33 In healthy articular cartilage, proliferation of chondrocytes is resisted whereas GAG production increases. 32 DNA content measurement revealed that there were no significant differences in the DNA content between the different groups after 21 days of culture. GAG/DNA showed that although the amount of synthesized GAG was significantly increased in the presence of TGF-β, there were no significant differences between tissue and gelatin scaffolds.…”
Section: Discussionmentioning
confidence: 84%
“…10 FTIR data proved an increase in the cross-linking degree in both tissue and gelatin scaffolds after treating with EDC/NHS. 32 Additionally, it seems that a considerable increase of COL II as the main component of the cartilage matrix is more likely to moderate this expression difference. 27 Thus, sensing matrix stiffness by the cells is likely to modulate differentiation into the various cell lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation